Pengaruh Gaya Kepemimpinan Dan Motivasi Terhadap Kinerja Karyawan Pada PT. Perkebunan Nusantara I Regional 1 - Muhammad Basri; Dody Salden Chandra (CERED Indonesia Institute, 2026)
The purpose of this study was to determine whether leadership style effects employee performance, to determine whether work motivation affects employee performance and to determine whether leadership style and motivation affect employee performance at PT. Perkebunan Nusantara I Regional 1. The population in this study were employees of PT. Perkebunan Nusantara I Regional 1 totaling 127 people, with a satured sample size of 127 employees. The data collection technique used in this study was a questionnaire. The analysis technique used in this study was multiple linear regression, classical assumptions, hypothesis testing and coefficient of determination. The results showed that there was a positive and significant influence of leadership style on employee performance, there was a positive and significant influence of motivation on employee performance and there was a simultaneous and significant influence of leadership style and motivation on employee performance at PT. Perkebunan Nusantara I Regional 1.